The Impact of Education Setup Towards Teachers’ Capability and Development Priority - Jaluague, Jucel Asis (FKIP Universitas Lampung, 2023)
The Impact of Education Setup Towards Teachers' Capability and Development Priority Objectives: This study used a mixed research design to assess the performances of the Senior High School Physical Education and Health teacher's capability and professional development priorities. Methods: The study used qualitative and quantitative data collection methods. The survey data on teachers' capability and priority development needs were analyzed using simple statistics such as mean and standard deviation. Following quantitative data analysis, qualitative data collection involved transcribing and analyzing the data. Findings: Teachers demonstrated a strong capability in assessment and reporting and plus factors. The identified priority development needs were in content knowledge and pedagogy, learning environment and diversity of learners, assessment and reporting, and plus factors. Besides, facilitating learning, insufficient training, and low standards for addressing students' specific needs. It negatively impacts teachers' confidence, increasing job frustration and affecting their teaching performance. Conclusion: The new education setup challenges teachers' capability and increases the need for development due to limited knowledge and skills. The results reveal the necessity for practical, appropriate, relevant, and timely training tailored to the student's context to ensure effective instructional delivery. Keywords: capability, content knowledge and pedagogy, learning environment and diversity of learners, curriculum and planning, assessment and reporting, and plus, priority development, self-assessmentDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202308